Fingerprint Salt & Pepper Noisy Image Enhancement with Threshold Method. Issue 1 (February 2021) - Ince, Mahmut; Lu, Songfeng; Alfadhli, Saad Ali; Maulood, Ismail; Alresheedi, Shayem Saleh
Abstract: We present an adaptive threshold method for salt and pepper noisy fingerprint images. At first, we applied a threshold algorithm to detect noisy and corrupt pixels. Fingerprint image optimized with window filter produced pixels values. We measured the quality of the fingerprint images with peak signal to noise ratio and other efficient noise removing techniques were compared with it. The result shows improving performance of our method with remove salt and pepper noise from a fingerprint image. Our present work is useful to reduce or minimize medium level noise in fingerprint image. In future, we will work to reduce more than 80 percent noise level in fingerprint image.